Transfer parameters for ICRP's Reference Animals and Plants in a terrestrial Mediterranean ecosystem. (June 2018) - Guillén, J.; Beresford, N.A.; Baeza, A.; Izquierdo, M.; Wood, M.D.; Salas, A.; Muñoz-Serrano, A.; Corrales-Vázquez, J.M.; Muñoz-Muñoz, J.G.
Abstract: A system for the radiological protection of the environment (or wildlife) based on Reference Animals and Plants (RAPs) has been suggested by the International Commission on Radiological Protection (ICRP). To assess whole-body activity concentrations for RAPs and the resultant internal dose rates, transfer parameters are required. However, transfer values specifically for the taxonomic families defined for the RAPs are often sparse and furthermore can be extremely site dependent. There is also a considerable geographical bias within available transfer data, with few data for Mediterranean ecosystems. In the present work, stable element concentrations (I, Li, Be, B, Na, Mg, Al, P, S, K. Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Se, Rb, Sr, Mo, Ag, Cd, Cs, Ba, Tl, Pb and U) in terrestrial RAPs, and the corresponding whole-body concentration ratios, CRwo, were determined in two different Mediterranean ecosystems: a Pinewood and a Dehesa (grassland with disperse tree cover). The RAPs considered in the Pinewood ecosystem were Pine Tree and Wild Grass; whereas in the Dehesa ecosystem those considered were Deer, Rat, Earthworm, Bee, Frog, Duck and Wild Grass. The CRwo values estimated from these data are compared to those reported in international compilations and databases. Highlights: CRwo data for 30 elements and 8 terrestrial RAPs in two Mediterranean ecosystems. Possible seasonal variation (1–2 orders of magnitude) in CRwo for Cs and Sr. CRwo for alkali (K, Rb and Cs) and alkali earth (Ca, Sr and Ba) decrease with increasing Z. CRwo for K and Ca were generally above those reported for temperate ecosystems.